Globalization and Liberalism : Montesquieu, Tocqueville, and Manent - Shelley, Trevor (Book collections on Project MUSE., 2020)
"In this learned and wide-ranging book, Trevor Shelley engages the controversial topic of globalization through philosophical exegesis of great texts. This study illustrates and defends the idea that at the heart of the human world-in thinking, reflecting, and acting-is the antinomy of the universal and the particular. Various thinkers have emphasized one aspect of this tension over the other. Some thinkers such as Rousseau and Schmitt have defended pure particularity. Others such as Habermas have uncritically welcomed the intimations of the world state. Against these twin extremes of radical nationalism and antipolitical universalism, this book seeks to recover a middle or moderate position, that is, the liberal position. To that end, Shelley traces a tradition of French liberal political thinkers who attempt to take account of both sides of the antinomy: Montesquieu, Tocqueville, and Manent. As Shelley argues, each of these thinkers in his own way defends the integrity of political bodies, denies that the universal perspective is the only legitimate one, and recognizes that, without differences and distinctions across the political landscape, self-government and freedom of action are impossible"--